Energy-Saving Design of Smart City Buildings Based on Deep Learning Algorithms and Remote Sensing Image Scenes (Informatica, 2024)
With the continuous development of society and economy, the construction of urbanization has promoted the continuous expansion of the scale of the city. The disorderly and rough land acquisition and construction has brought about the problems of inefficient use of many resources, which are in line with the concept of green and smart construction. Violated. In response to these shortcomings and needs, this article introduces deep learning algorithms and remote sensing image scenes. Based on the business logic of smart city building energy-saving design, the data set is analyzed by category according to different types of supervision and deep learning to realize the smart city. Effective analysis of building energy efficiency, and a simulation quantitative experiment for evaluation, using BIM technology to analyze the energy-saving design of office buildings, to achieve further optimization of energy-saving design. The simulation experiment results show that the deep learning algorithm and remote sensing image scene are effective and can support the energy-saving design of smart city buildings.